Effect of Nb additive on wear resistance and tensile properties of the hypereutectic Fe-Cr-C hardfacing alloy. (September 2020) - Liu, Sha; Shi, Zhijun; Xing, Xiaolei; Ren, Xuejun; Zhou, Yefei; Yang, Qingxiang
Graphical abstract: Highlights: The microstructures and phase structures of hypereutectic Fe-Cr-C hardfacing alloy with and without Nb additive were observed and determined. The wear resistance was improved by the refinement effect of Nb. The tensile strength parallel to the primary (Fe, Cr)7 C3 was improved by the refinement effect of Nb, while that vertical to the primary (Fe, Cr)7 C3 was lowered. Abstract: The effects of Nb additive on wear resistance and tensile properties of the hypereutectic Fe-Cr-C hardfacing (harden-surface-welding) alloys were investigated. The microstructures and phase structures of the alloys with and without Nb additive were compared by means of optical microscopy (OM) and X-ray diffractometer (XRD). The wear behaviors were measured by reciprocating wear tests via CSM Tribometer. The tensile properties were measured by universal testing machine. In order to investigate the (Fe, Cr)7 C3 carbides refinement by Nb additive, the formation thermodynamics of NbC and the misfit between NbC and (Fe, Cr)7 C3 were calculated. The results show that the alloy with Nb additive contains NbC as well as (Fe, Cr)7 C3 and γ-Fe. The size of the primary (Fe, Cr)7 C3 carbides in the alloy with Nb additive is obviously smaller than that without Nb additive. The mass loss of the alloy with Nb additive is less than that without Nb additive. The worn surfaces also indicate that the amount of the cracks on the alloy surface with Nb additive is less than that without Nb additive. The tensile strength parallel to the rod-like primary (Fe, Cr)7 C3 carbides is larger than that vertical to the primary (Fe, Cr)7 C3 carbides. The tensile strength parallel to the primary (Fe, Cr)7 C3 carbides of the alloy with Nb additive is larger than that without Nb additive, while the tensile strength vertical to the primary (Fe, Cr)7 C3 carbides of the alloy is lower than that without Nb additive. The phase fraction vs. temperature curves of the alloy shows that the alloy with Nb additive preferentially forms NbC and then primary (Fe, Cr)7 C3 carbides. The lattice misfit between NbC and (Fe, Cr)7 C3 is 2.16%, which proves NbC can be as the heterogeneous nucleus to refine primary (Fe, Cr)7 C3 carbides in the Fe-Cr-C hardfacing (harden-surface-welding) alloy.